Eflornithine – new possibilities in treatment of hirsutism and hypertrichosis. - Prędota, Agata; Imko-Walczuk, Beata (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction. Excessive hair may present as hirsutism or hypertrichosis. Hirsutism is defined as the occurrence of excessive hair growth in women in localizations specific for men such as the chin, upper lip, abdomen, chest and thighs. Hypertrichosis is excessive hair growth associated with the transformation of the follicular hair into keratinized structure. Hirsutism may be a manifestation of many systemic diseases. Treatment of hirsutism comprises pharmacological and mechanical methods. Drugs used for the therapy of hirsutism can be divided into inhibitors of androgens, antiandrogens and oral hypoglycemic agents that reduce insulin resistance. Mechanical methods include shaving, bleaching, waxing, hair removal using creams, electrolysis and laser depilation. Recently in the literature there have been reports on a new substance – eflornithine – in the treatment of hirsutism in women. Objective. Presentation of a 24-year-old woman with hirsutism, treated with eflornithine cream. Case report. The patient has a history of irregular menstrual cycles, Hashimoto's disease, hyperprolactinemia since 2004, with hypertrichosis on the face, neck, linea alba and nipples for 9 years. She was hospitalized in the Department of Endocrinology and Internal Medicine, Medical University of Gdańsk with a diagnosis of idiopathic hirsutism. She consulted a dermatologist due to severe hirsutism affecting her mental state. In the past, the patient was treated with laser therapy and electrocoagulation with no effect. Due to the patient’s reluctance to undergo previous treatments and the presence of dark, heavy hair in prominent places, we decided to introduce therapy with eflornithine cream applied 2 times a day for selected areas. Treatment was continued up to 8 weeks with a recommendation for further therapy, but the patient stopped it for financial reasons (the high cost of the product). Conclusions . Treatment with eflornithine cream 2 times a day within 8 weeks caused reduction of 60% of hair on the face, nipples and abdomen, and 30% on the neck.